Impact of Jigsaw Instructional Strategy on Achievement Among Junior Secondary School Students in Lagos State - Okudo, Afoma Rosefelicia; Ughelu, Jennifer N. L. (PEDAGOGIA, 2024)
The Igbo language, one of Nigeria's major indigenous languages, plays a vital role in the lives of many Nigerians and their educational development. Recognizing its importance, the Nigerian government incorporated Igbo language teaching into the National Policy on Education (NPE), mandating its inclusion in the school curriculum. This study examined the impact of the Jigsaw Instructional Strategy (JIS) on the achievement of junior secondary school students in Igbo language and culture in Lagos State, Nigeria. Adopting a descriptive survey and quasi-experimental design, the study raised two research questions and tested one hypothesis. The sample consisted of 48 Junior Secondary School II students from a purposively selected school in Amuwo Odofin Local Government Area, Lagos State. Instruments included the Pre- and Post-test Igbo Language Achievement Test (ILAT) and Jigsaw Perception Assessment Questionnaire (JPAQ), with a reliability coefficient of 0.83. Data were analyzed using descriptive statistics and t-tests at a 0.05 significance level. Results indicated a significant positive impact of JIS on students’ achievement in Igbo, with noticeable improvements compared to the conventional instructional method. Based on these findings, it is recommended that Igbo language curriculum developers incorporate JIS into teacher training programs and that educational stakeholders encourage its adoption to enhance classroom instruction and learning outcomes.